Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.

French Immersion Teen Camp : Feasibility Study - Newcombe, Vanessa; Roberts, Carla; Griffin, Emily (Coasters Association, 2008)
Living in such an isolated area such as, the Lower North Shore, there is a lack of activities for all ages, but more so for the adolescent age. There are very few activities on the Lower North Shore that directly focuses on teenagers, so teens resort to other activities that result in social problems (i.e. drinking, drugs, vandalism, etc…). Therefore, a French Immersion Teen Camp would provide teenagers with activities and a program that is especially designed for them. Teenagers could have a chance to get away from the social problems and into a program that will nurture and develop a safe and healthy environment in which the teens can improve their health and obtain skills that will assist them in their future lives and also promote and develop their French as a Second Language skill.

Delivering Health and Social Services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009 : Translated and Edited Version - Jeffery Hale - Saint Brigid's (JHSB) (2008)
To comply with the latter, the Capitale-Nationale Region's Health and Social Services Network Development Agency (CNR Agency) launched a review of the health and social services offered in English to English speakers in the region.

Executive Summary of the Document "Delivering Health and Social services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009" - Jeffery Hale - Saint Brigid's (JHSB) (2008)
Between June and November 2006, the Agency Responsible for Health and Social Services in Québec's Capitale-Nationale region (or the CNR Agency) prepared a comprehensive Access Program report. This document details how health and social services are delivered in English to English speakers in the greater Quebec City region.

Questions and Answers about Access to Health and Social Services in English in the Capitale-Nationale Region (CNR) - Jeffery Hale - Saint Brigid's (JHSB) (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2008)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

The Twenty-Seventh Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2008)

Lost in Translation - Buffitt, Kimberly; Lanyi, Danille (CARPI Conference, 2008)

CHSSN Telehealth Program & Follow-up Intervention Project : 2007-2008 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2008)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

Going... Going... Gone : The Decline of English-language Production in Quebec 1996-7 to 2006-7 - Magnetic North Associates (2008)
English-language production in Quebec has fallen by 40% since the peak production years ended in 2000. Total certified English-language production in Canada has been stagnant or declining since peak production ended in 2000. From 1999-0 to 2005-6, total English production in Canada fell by 10%. English-language production in Quebec has suffered the most dramatic decline during this period.

The Training and Retention of Health Professionals Project - Dialogue McGill (2008)

The Baseline Data Report 2007-2008 : Quebec's Social and Health Survey Information - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2008)
The Health and Social Services Networking and Partnership Initiative (HSSNPI) is a funding program of the Quebec Community Groups Network mandated by Health Canada as a measure of the Federal Action Plan for Official Language Communities. The HSSNPI aims to support the creation of durable links and joint action between English-speaking communities and Quebec’s health and social services system. The Baseline Data Report is a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the health status and vitality of Quebec’s English‐speaking population. The report is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders to develop strategies to improve the well‐being of their constituencies.
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2008)

Dialogue : Better Communication for Better Care - Dialogue McGill (2008)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2008)

Developing an Arts, Culture and Heritage Policy Framework for English-speaking Quebec - English Language Arts Network (ELAN) (2008)
This policy describes the philosophy, principles, development guidelines, priorities and operational considerations that English-speaking Quebec intends to pursue in the coming years to develop and disseminate the its different forms of cultural expression: It includes ideas that could engage a wide variety of different organizations in pursuing the full implementation of this policy.
Keywords: Official Language Minority Community (OLMC)

Ancestors : Life, Death, and Descendants of Quebec City's Anglophones - Morrin Centre (2008)
Quebec City’s cemeteries have lots to say about our ancestors and the past. They are places of remembrance for those close to the departed, but they are also a storehouse of memories for the whole community. Cemeteries are closely linked to religious belief : They express a particular vision of the world, a set of values and a culture.

Building the City : The Influence of English Speakers on Quebec City's Architecture - Morrin Centre (2008)
Quebec City is praised for its quintessential Frenchness, yet a closer look at its architecture reveals a city with a strong British influence. Ninety-five per cent of the city was built or modified after the British conquest in 1759. In the middle of the ninete nth century, half the people in the Upper Town were English speakers, and they left a clear mark on the built environment. Many of the city’s important landmarks, from the Château Frontenac to the Price Building, were designed by English-speaking architects.

Les ancêtres : vie, mort et descendance des anglophones de la ville de Québec - Morrin Centre (2008)
Les cimetières de la ville de Québec constituent une mine de renseignements précieuse à propos de nos ancêtres et du passé. Ils sont des lieux de mémoire, tant pour les proches des disparus que pour la collectivité. Étroitement liés à une religion, les cimetières sont l’expression tangible d’une vision du monde, d’un ensemble de valeurs, d’une culture.

Les bâtisseurs : l'influence anglophone sur l'architecture de Québec - Morrin Centre (2008)
Bien que l’on vante le caractère français de Québec, son architecture a subi une influence anglaise considérable : 95 % des édifices sont construits ou modifiés après 1759, suite à la Conquête. Au milieu du 19e siècle, la moitié des habitants de la Haute-Ville sont anglophones et leur présence marque le patrimoine bâti de la ville. De nombreux monuments caractéristiques de Québec, du Château Frontenac à l’édifice Price, sont conçus par des architectes anglophones.

Les gens de foi : la vie religieuse des anglophones à Québec - Morrin Centre (2008)
Cette visite vous permet d’en apprendre plus sur les anglophones de Québec à travers la découverte de leurs lieux de culte et de leurs pratiques religieuses. Les distinctions entre les différentes croyances seront examinées et vous aurez ainsi une meilleure compréhension du paysage religieux de Québec.

Les gens du fleuve : la vie des anglophones sur les rives du Saint-Laurent - Morrin Centre (2008)
L’historien grec Hérodote disait de l’Égypte qu’elle était un « don du Nil » tant ce fleuve était important dans la vie des Égyptiens. De la même façon, on pourrait dire que Québec est un don du Saint-Laurent. Le Saint-Laurent était le « boulevard » des Autochtones, premiers habitants du territoire, avant de devenir la voie d’accès des explorateurs Français. Il est un facteur déterminant dans le choix de Samuel de Champlain d’établir une colonie à Québec, car il y voyait une route vers la Chine.

People and Faith : The Religious Life of English Speakers in Quebec City - Morrin Centre (2008)
Through this tour, you’ll learn about Quebec City’s anglophones through their places of religious worship and practice. We’ll look at distinctions between different forms of belief and you’ll gain a better understanding of Quebec’s religious landscape.

People of the River : Anglophone Life on the St. Lawrence - Morrin Centre (2008)
The Greek historian Herodotus summed up Egypt’s dependence on its great river by calling the country a “gift of the Nile.” In the same way, it could be said that Quebec is a gift of the St. Lawrence. The St. Lawrence was the “boulevard” of the territory’s first inhabitants, the Aboriginal people. Then it became the access route for French explorers. Samuel de Champlain thought it was a route to China, and this was a determining factor in his decision to found a colony at Quebec.

Rediscover Quebec City's Anglo Heritage Through Four Self-Guided Tours / Redécouvrez le visage anglophone de Québec à l'aide de quatre visites autoguidées - Morrin Centre (2008)

A Policy Framework for Economic Development and Employability for the English-speaking Communities of Quebec : Submitted to the Quebec Community Groups Network (QCGN) - Qu'anglo (2008)
Through previous research and following a number of community consultations, the QCGN had determined that there is a need for initiatives that will enable the English-speaking Communities of Quebec to work more effectively with the Government of Canada, the Government of Quebec, school boards and relevant stakeholders to more fully participate in the economy of province. Given the continuing exodus of educated and trained anglophones to seek employment opportunities elsewhere, and the difficulties faced by particular segments of the population, especially youth, visible minorities and newly arrived immigrants, who choose to seek employment and self-employment within Quebec, it was determined that an integrated and targeted approach to improve the economic development prospects of the community was required.
Keywords: Official Language Minority Community (OLMC)

Adult ESL and Literacy : Issues and Options - Spruck Wigley, Heide (The Centre for Literacy of Quebec (CFL), 2008)
In this paper, I would like to put forward a number of issues for us to think about and discuss. At the same time, I argue for a better articulated system that more closely matches the needs and goals of various subgroups of English language learners.